Mastering the Art of Arguments - Kamariah Hammonds (Journal of College Orientation, Transition, and Retention)
Bo Seo’s Good Arguments teaches its readers how to properly deconstruct, analyze, and listen to arguments inside and outside of debate competitions. Moving the focus away from competition, debate is one of the many ways Student Affairs Professionals, specifically those involved in orientation, retention, and transition, can further teach college students to proactively and authentically communicate, be effective leaders, and apply critical thinking skills upon entering college and the adult world.